The Roles of Information and Communication Technology (ICT) in Transforming Students Learning Outcomes at STMIK DCI Tasikmalaya - Andri Sukmaindrayana; Aneu Yulianeu (Jurnal Iqra' : Kajian Ilmu Pendidikan, 2022)
This study aimed to gain an in-depth understanding of the teaching system at STMIK DCI Tasikmalaya, especially the role of information and communication technology in transforming student learning outcomes. The data sources consist of three sources: interviews with academics, documentation, and field observations. After getting the data, the researchers tried to analyze using phenomenological approach, namely trying to understand from a series of existing data such as coding the data, evaluating the data, and reporting as data as well as interview data that report in text form. Based on the results, the researchers concluded that the students in using ICT could transform the student learning outcomes, for instance have a good skills in computers. They had also used it to solve the problemhe problems in class and they had planned for the benefit of supporting career tools in the future. The adoption of technology could provide convenience for students for lecturers in finding data, processing data, and synthesizing and communicating data in learning. Likewise, transforming technology was not only learning outcomes but also its ability to assist academics in evaluating student learning outcomes to make the parties work optimally. Keywords: Students Learning Outcome, Communication Technology, Information Technology